Digital Marketing Socialization for Home Industry Actors in Winduhaji Village-Kuningan Regency: Sosialisasi Digital Marketing pada Pelaku Industri Rumahan di Desa Winduhaji-Kabupaten Kuningan - Indrawan, Rizki; Iman Teguh; Oktaviani Rita Puspitasari; Dea Amara; Cahyo Aji Pangestu (Universitas Lancang Kuning, 2025)
Winduhaji Village has great potential in the home industry, but the limitations of digital literacy are the main challenge for MSME actors to develop their businesses. This community service program aims to increase MSME actors' understanding of digitalization and digital marketing through socialization, interactive education, and practical training. This activity was attended by 20 MSME actors with diverse business backgrounds. The results showed a significant improvement in participants' understanding and skills, such as the ability to use social media and e-commerce platforms for marketing. Post-activity evaluations showed a positive response from participants to the relevance and benefits of the program. In conclusion, this program has succeeded in increasing the competitiveness of MSMEs in Winduhaji Village, although it still takes longer for optimal results.